Ks. Prof. Walerian Meysztowicz i Polski Instytut Historyczny w Rzymie - Supruniuk, Mirosław Adam (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2013)
FATHER. PROF. WALERIAN MEYSZTOWICZ AND THE POLISH HISTORICAL INSTITUTE IN ROME The professors of the Polish University in Vilnius, which operated in 1919–1939, after 1945 played a major role in the Polish science during emigration. One of the professors from Vilnius was father Walerian Meysztowicz, theologian, and a publisher of primary sources. Even before the war he became a diplomatic counselor of the Polish Embassy in Vatican. During the war he resided in Vatican, and after it in Rome. In 1945 along with other Polish scholars he brought the Polish Historical Institute in Rome into existence. The Institute carried out research, organized conferences and meetings, and, most importantly, published the magazines Antemurale and a series of sources Elementa ad fontium editiones—which published documents on the history of Poland and the catholic church in Middle Europe from Italian, Spanish, French and German Archives.